Legal Aspects of Liability of Participants (Shareholders) of Joint Stock Companies in the Republic of Uzbekistan for Breach of Corporate Obligations - Habibullayev, Asliddin (Indonesian Journal Publisher, 2024)
This article considers legal aspects of liability of participants (shareholders) of joint stock companies in the Republic of Uzbekistan for breach of corporate obligations. The article analyses both national normative legal acts and international standards and practices of regulation of shareholders' liability. The author has considered issues related to mechanisms for protecting the rights of shareholders and creditors, as well as imposing sanctions on shareholders for breach of corporate obligations. In addition, recommendations were made to improve legislation in this area.